Non-invasive super-resolution imaging through dynamic scattering media - Dong Wang (Nature Portfolio, 2021)
The authors introduce stochastic optical scattering localization imaging (SOSLI) for non-invasive super-resolution imaging through scattering media. They capture multiple speckle patterns of photo-switchable point sources and use the speckle correlation to retrieve images with 100 nm resolution.